2009
DOI: 10.2495/air090141
|View full text |Cite
|
Sign up to set email alerts
|

Application of mineral magnetic concentration measurements as a particle size proxy for urban road deposited sediments

Abstract: The application of mineral magnetic concentration parameters (χ LF , χ ARM and SIRM) as a potential particle size proxy for urban road deposited sediment collected from Scunthorpe, North Lincolnshire, U.K. has been investigated. Correlation analyses between each magnetic parameter and traditional particle size classes (i.e. sand, silt and clay) and respiratory health related size classes (i.e. PM 10 , PM 2.5 and PM 1.0 ) are reported. Significant relationships (p <0.01; n = 35) exist between clay content and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Booth et al [32] revealed PM 10 Marylebone Road displays similar correlation significance levels to those of the towns of both Southport [32] and Scunthorpe [33]. However, a notable discrepancy in the correlations is that Marylebone Road again displays significant negative trends; whereas, both of the other places have significant positive trends.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Booth et al [32] revealed PM 10 Marylebone Road displays similar correlation significance levels to those of the towns of both Southport [32] and Scunthorpe [33]. However, a notable discrepancy in the correlations is that Marylebone Road again displays significant negative trends; whereas, both of the other places have significant positive trends.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, this venue was selected so as to validate the potential of adopting an alternative technology for monitoring the PM sizes of RDS. Previous RDS studies, elsewhere, have already shown kinships exist between particle sizes and heavy metal content [28][29][30][31] but the magnetic signature of RDS has only recently been identified to exhibit significant correlations with these characteristics [32,33]. However, magnetotechniques have not been widely applied to sites where there are known PM issues and, thus, allow new findings, herein, to be compared with other studies.…”
Section: Introductionmentioning
confidence: 84%
“…The statistical relationship between Cu and Zn (r = 0.69) in the soils studied can confirm the above hypothesis (Table 4). According to [97,98], the correlations between the contents of some components enable indicating their potential sources. A strong positive correlation between almost all metals indicates similar sources.…”
Section: Identification Of Pollution Sources Using Statistical Analysesmentioning
confidence: 99%
“…A strong positive correlation between almost all metals indicates similar sources. Generally, an increase in elemental contents compared to background levels indicates anthropogenic influences [98]. Metals such as Cd, Cu, Pb, and Zn are good indicators of soil contamination because they are present in gasoline, automotive components, lubricating oils, and industrial exhaust [22].…”
Section: Identification Of Pollution Sources Using Statistical Analysesmentioning
confidence: 99%
“…Correlation matrixes for chemical properties and heavy metals in soils of selected primary school playgrounds: The correlation between the concentrations of some geochemical parameters can establish influencing factors and indicate potential sources of pollution (Robertson et al, 2003;Crosby, 2012) in Otari and Dabiri, (2015). The result of the correlation analysis between the parameters showed that there was a positive correlation between the elements with regards to their sources and origin.…”
Section: Biose E; Amaechi Cf; Nwaemene Cmentioning
confidence: 99%